Complementary Use of Cultivation and High-Throughput Amplicon Sequencing Reveals High Biodiversity Within Raw Milk Microbiota - Breitenwieser, Franziska; Doll, Etienne V.; Clavel, Thomas; Scherer, Siegfried; Wenning, Mareike (Frontiers in Microbiology, 2020)
Raw milk microbiota are complex communities with a significant impact on the hygienic, sensory and technological quality of milk products. However, there is a lack of knowledge on factors determining their composition. In the present study, four bulk tank milk samples of two farms at two different time points were analyzed in detail for their microbiota using cultivation and 16S rRNA amplicon sequencing. Diversity in samples from the first time point were was assessed via cultivation of 500 aerobic mesophilic bacterial isolates in each sample. A high biodiversity of 70 and 110 species per sample was determined, of which 25-28% corresponded to yet unknown taxa. These isolates were dominated by Gram-positive members of the genera Staphylococcus, Corynebacterium, Streptococcus or Janibacter, whilst Chryseobacterium and Acinetobacter were most abundant among the Gram-negative taxa. At the second time point, samples of the same farms were analyzed via both cultivation (1,500 individual colonies each) and high-throughput 16S rRNA gene amplicon sequencing. The latter revealed a 3-fold higher biodiversity at the genus level, as anaerobic or fastidious species were also detected. However, cultivation identified genera not captured by sequencing, indicating that both approaches are complementary. Using amplicon sequencing, the relative abundance of a few genera was distorted, which seems to be an artifact of sample preparation. Therefore, attention needs to be payed paid to the library preparation procedure with special emphasis on cell lysis and PCR.